Competition under Incomplete Contracts and the Design of Procurement Policies - Carril, Rodrigo; Gonzalez-Lira, Andres; Walker, Michael S. (American Economic Review, 2026)
We study the effects of intensifying competition for contracts in the context of US Defense procurement. Leveraging a discontinuous regulation that mandates agencies to publicize certain contract opportunities, we document that expanding the set of bidders reduces award prices but deteriorates post-award performance in terms of cost overruns and delays. We develop and estimate an auction model with endogenous entry and stochastic execution performance, in which the buyer endogenously chooses the intensity of competition. Model estimates indicate substantial heterogeneity in performance across contractors and show that simple adjustments to the current regulation could provide significant savings in procurement spending. (JEL D22, D24, D44, D82, D86, H56, H57)